2007
DOI: 10.1016/j.drugalcdep.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Income generating activities of people who inject drugs

Abstract: Background-Injection drug users (IDU) commonly generate income through prohibited activities, such as drug dealing and sex trade work, which carry significant risk. However, little is known about the IDU who engage in such activities and the role of active drug use in perpetuating this behavior.Methods-We evaluated factors associated with prohibited income generation among participants enrolled in the Vancouver Injection Drug Users Study (VIDUS) using logistic and linear regression. We also examined which sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
159
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(182 citation statements)
references
References 30 publications
21
159
0
2
Order By: Relevance
“…This result is consistent with other studies that showed significant associations between illegal or marginal income sources and injection risk behaviours or risky patterns of drug use (Richardson et al, 2010;DeBeck et al, 2007;. For instance, in Vancouver, such sources of income have been linked to daily heroin injection (Richardson et al, 2010;Debeck et al, 2007;, injecting in public places (Richardson et al, 2010;DeBeck et al, 2011), binge drug use and syringe sharing (DeBeck et al, 2011). For drug residue injection, it can be hypothesized that, compared to legal income sources, marginal or criminal sources of income likely produce more irregular or weak income streams, which could force PO injectors to fall back on PO residues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with other studies that showed significant associations between illegal or marginal income sources and injection risk behaviours or risky patterns of drug use (Richardson et al, 2010;DeBeck et al, 2007;. For instance, in Vancouver, such sources of income have been linked to daily heroin injection (Richardson et al, 2010;Debeck et al, 2007;, injecting in public places (Richardson et al, 2010;DeBeck et al, 2011), binge drug use and syringe sharing (DeBeck et al, 2011). For drug residue injection, it can be hypothesized that, compared to legal income sources, marginal or criminal sources of income likely produce more irregular or weak income streams, which could force PO injectors to fall back on PO residues.…”
Section: Discussionsupporting
confidence: 93%
“…One marker is income, for which PO residue injectors had greater odds of reporting marginal or criminal activity (such as drug dealing, sex work, panhandling) as their main source of income. This result is consistent with other studies that showed significant associations between illegal or marginal income sources and injection risk behaviours or risky patterns of drug use (Richardson et al, 2010;DeBeck et al, 2007;. For instance, in Vancouver, such sources of income have been linked to daily heroin injection (Richardson et al, 2010;Debeck et al, 2007;, injecting in public places (Richardson et al, 2010;DeBeck et al, 2011), binge drug use and syringe sharing (DeBeck et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…An observational study by DeBeck et al 7 pointed to the economic relationship between intravenous drug use and income generation by prostitution, and noted that intervention to relieve financial pressure by involvement in treatment programmes should, on the face of it, be successful. A further study 8 pointed to the improved take-up of a wider range of health promotion interventions, which is likely if these are embedded in a drug treatment programme and continued untreated illicit drug use is a barrier to exiting prostitution.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…(Immervoll, 2009;Nelson, 2004;Walker, 2004) Higher income may improve individual health outcomes through its direct influence on material conditions (ability to work, housing, health care access and nutrition) and indirectly by enabling control over life situations. (Deaton, 2002;Marmot, 2004) However, observational studies have found that higher income among PWUD is also associated with high-intensity drug use (Bretteville-Jensen & Sutton, 1996;DeBeck et al, 2007;Deschenes & Anglin, 1991;Grapendaal, Lewu, & Nelen, 1995;Sherman & Latkin, 2002), suggesting a more complex relationship between income and drug use. While this association may be explained in part by the need for individuals with higher intensity drug addiction to generate more income in order to meet their drug use needs (Bourgois, 1998;Deering et al, 2013;Maher, 1997), observational studies also suggest that some income generation strategies can contribute to higher intensity drug use or create additional barriers to decreasing drug use.…”
Section: Introductionmentioning
confidence: 99%